USING AQUATIC PLANTS FOR DEGRADATION OF TSS, BOD AND COD IN DOMESTIC WASTEWATER, Actinoscirpusgrossus IN FLOATING TREATMENT WETLAND SYSTEMS (FTWs) - Syafrizal Syafrizal; Suhendrayatna Suhendrayatna; Muhammad Zaki; M. Nasir (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Wetlands, as part of ecological technology commonly applied in wastewater treatment, are an innovative solution in environmental protection and restoration. Floating Treatment Wetland Systems (FTWs) are a new concept in wastewater treatment using macrophytes rooted in aquatic plants modified as floating systems. Use of a local aquatic plant that is often found and thrives as a weed in rice fields throughout Aceh, namely Actinoscirpusgrossus. Variables varied according to plant height, pond I 90cm – 150cm, pond II 50cm – 90cm and pond III control without plants, influent and effluent were analyzed every two weeks for 18 weeks with 9 analytical sampling times. The results of the domestic wastewater experimental parameter test showed that the average degradation efficiency (%DE) was pH 6.92, total suspended solid (TSS): 98.28%, biological oxygen demand (BOD): 97.77% and chemical oxygen demand (COD): 98.30%, very significant results. The management process of regularly cutting plants is an important part for the Actinoscirpusgrossus aquatic plant to achieve optimum results in processing wastewater, namely for 112 days with a maximum plant growth height of 165cm and 173cm for the two variations of the experimental ponds.